2021
DOI: 10.1186/s12966-021-01114-x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of on-shelf sugar labeling on beverage sales in the supermarket: a comparative interrupted time series analysis of a natural experiment

Abstract: Background Nutrition labels show potential in increasing healthy food and beverage purchases, but their effectiveness seems to depend on the type of label, the targeted food category and the setting, and evidence on their impact in real-world settings is limited. The aim of this study was to evaluate the effectiveness of an industry-designed on-shelf sugar label on the sales of beverages with no, low, medium and high sugar content implemented within a real-world supermarket. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 43 publications
1
4
0
Order By: Relevance
“…Our labels were smaller (and arguably more realistic) than have been tested in some previous studies [ 21 ]. Similar to our findings, a recent natural experiment in a real-world Dutch supermarket chain found that industry-designed on-shelf labels indicating the sugar content of non-alcoholic beverages using a colour-coded system (blue [lowest sugar content], green, yellow, amber [highest sugar content]) did not affect sales [ 34 ].…”
Section: Discussionsupporting
confidence: 88%
“…Our labels were smaller (and arguably more realistic) than have been tested in some previous studies [ 21 ]. Similar to our findings, a recent natural experiment in a real-world Dutch supermarket chain found that industry-designed on-shelf labels indicating the sugar content of non-alcoholic beverages using a colour-coded system (blue [lowest sugar content], green, yellow, amber [highest sugar content]) did not affect sales [ 34 ].…”
Section: Discussionsupporting
confidence: 88%
“…So far, few SSB products high in sugar have provided sugar content information on the NFP in China [ 48 ]. Nutritional labeling is a vital tool to promote healthier choices, while the previous evidence has suggested that compulsorily added new nutritional information (e.g., added sugars and percent daily values for added sugars) alone would not be sufficient to affect choices of beverages [ 49 , 50 ], and consumers might be required to improve their perceptions on healthy choices and their capability to interpret the information in nutritional labeling via health education and promotion, so as to use it frequently [ 51 ]. To reduce the SSB consumption rates among preschoolers, the use of evidence-based measures aiming to improve parental awareness of the health effects of SSBs and to improve their self-efficacy to choose healthier drinks [ 52 , 53 , 54 , 55 ] may be an indispensable strategy.…”
Section: Discussionmentioning
confidence: 99%
“…A similar study with MTL was carried out in an online supermarket in Australia [ 15 ], but there was no evidence that the FOP labels led to an increase in sales of healthier foods after 10 weeks. A recent study from the Netherlands evaluated the effectiveness of an industry-designed on-shelf sugar label on the sales of beverages with no, low, medium and high sugar content implemented within a real-world supermarket [ 16 ]. The study found that this label did not significantly decrease unhealthy beverage sales or significantly increase healthier beverage sales [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study from the Netherlands evaluated the effectiveness of an industry-designed on-shelf sugar label on the sales of beverages with no, low, medium and high sugar content implemented within a real-world supermarket [ 16 ]. The study found that this label did not significantly decrease unhealthy beverage sales or significantly increase healthier beverage sales [ 16 ]. Two studies were carried out with Guiding stars attached to the shelves adjacent to the foods in supermarket chains in Canada and the USA.…”
Section: Discussionmentioning
confidence: 99%